Bioenergy sustainability in the global South: Constraints and opportunities - Brady, M.A.; Sharma, S.; Baral, H.; Nasi, R. (CIFOR-ICRAF, 2023)
Many countries have recently adopted bioenergy as part of a critical strategy to reduce greenhouse gas (GHG) emissions to meet targets under the Paris Climate Agreement. Because of increased efficiency and lower production costs, along with legislative support and investment incentives, bioenergy use is swiftly becoming a renewable energy substitute for fossil fuels. The study provides a better understanding of bioenergy issues, potential and sustainability to inform countries in the global South and provide guidance on integrating bioenergy into their national energy plans by proposing a simplified sustainability framework for wood-based bioenergy.